Non‐selective beta‐blockers are not associated with increased mortality in cirrhotic patients with ascites. (30th March 2017) - Onali, Simona; Kalafateli, Maria; Majumdar, Avik; Westbrook, Rachel; O'Beirne, James; Leandro, Gioacchino; Patch, David; Tsochatzis, Emmanuel A.
Abstract: Background & Aims: Controversy exists on the impact of non‐selective beta‐blockers (NSBBs) on survival in patients with ascites. We assessed whether NSBB treatment affects survival in a cohort of 316 consecutive patients with ascites undergoing evaluation for liver transplantation. Methods: Consecutive patients with cirrhosis and ascites assessed for liver transplantation between 2011 and 2014 were retrospectively evaluated. Competing risk Cox regression analysis in the whole population and in propensity score matched patients were performed to identify predictors of survival. Results: Three hundred and sixteen patients were evaluated: males 229 (73%), mean age 54 years, median follow‐up: 7 months. Refractory ascites was diagnosed in 124 (39%) patients. Patients receiving NSBBs (n=128, 40.5%) had a higher frequency of previous spontaneous bacterial peritonitis (27% vs 17%, P =.025), lower frequency of refractory ascites (32% vs 44%, P =.03) but similar MELD and UKELD scores. Overall 80 (25%) patients died: 20 (16%) in the NSBB group vs. 60 (32%) in the non‐NSBB group ( P =.002). In multivariate competing risk Cox regression analysis, NSBB use was associated with reduced mortality (HR=0.55, 95% CI=0.33‐0.94) along with prophylactic antibiotic use (HR=0.33, 95% CI=0.14‐0.74), MELD score (HR=1.10, 95% CI=1.06‐1.14) and sodium levels (HR=0.94, 95% CI: 0.89‐0.98). No impact on survival was found when considering only patients with refractory ascites (NSBB use: HR=0.43, 95% CI=0.20‐1.11). Conclusions: Patients with ascites on NSBBs did not have impaired survival compared to those not receiving NSSBs and interestingly this observation was also confirmed in the subgroup with refractory ascites. Our results suggest that NSBBs are not detrimental, but instead seem safe even in more advanced stages of cirrhosis in patients on a transplant waiting list.